Faktor Keamanan Pangan Padapemakaian Aplikasi Pengantaran Makanan (FDAs) Pada Era Pandemi di Jakarta - Sri Hartono; Salim, Agus; Alamsyah , Zeffry (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
The COVID-19 pandemic encourages people to use alternatives to reduce interaction barriers, one of which is using the internet network. The pandemic has given blessings to business people in the food sector, due to the increase in orders through food delivery applications or Food Delivery Apps (FDAs). This condition creates new problems related to the health aspects of the food delivered because of the potential for virus transmission in the food delivered. The research focuses on the level of customer satisfaction which is influenced by food safety, level of trust, performance expectations and technology suitability. The population in this study is 10 million people who live in Jakarta and the sample in this study is 210 respondents. The sampling technique used was convenience sampling. Smart PLS software is used to process the data. Based on the test result, the six hypotheses are all accepted, and this supports previous research. This study expands the knowledge and benefits of food delivery using food delivery applications or FDA which creates user perceptions and behavior, together with technological factors influencing consumer trust and satisfaction to use FDA in the COVID-19 pandemic conditions. Keywords: FDAs, food safety, satisfaction technology suitability, trust